Preliminary study of potato varieties and hybrids laboratory resistance to Phytophthora infestans Mont. de Bary in the Primorsky Territory - N. V. Matsishina; A. S. Didora; O. A. Sobko; I. V. Kim; D. I. Volkov (Овощи России)
Relevance. Late blight (Phytophthora infestans Mont. de Bary) is one of the most harmful, rapidly spreading potato fungal diseases, which dramatically reduces its yield and affects tubers during storage. The quantitative manifestation of partial resistance within the same potato variety depends on meteorological conditions and the infectious load. Therefore, its objective assessment is obtained when testing varieties in regions that are stably favorable for the development of pathogens (Sakhalin Island and central Mexico), or in standard laboratory conditions using climatic chambers and molecular genetic methods. The aim of this work was a laboratory assessment of the potato varieties and hybrids resistance to late blight.Methods. Data on laboratory assessment of the potato varieties and hybrids resistance to late blight are presented. The experiment was carried out using generally accepted methods for the study and assessment of the potato varieties resistance to phytopathogens with minor modifications.Results. It was established that the varieties Smak, Yantar, Dachny and Kazachok are medium susceptible to late blight, as shown in the Catalog of varieties. In the variety specimen Pri-12-35-4, with a low degree of necrosis and sporulation development, slices showed damage to 50% of the tubers surface with active sporulation and maturation of double-flagellated zoospores. Hybrids Pri-11-12-5, Pri-12-18-7 showed a high score for the development of necrosis and sporulation with a slight excess to these indicators for tubers (1.17-1.05 times). Among hybrids and varieties of potatoes, a sample of Pri-11-31-24 stood out, with an average score for sporulation and slice necrosis of 1.44 and 1,42, respectively, for tuber damage - 1,72.